Analysis of double loops discrete single input fuzzy for single phase inverter - Md. Ayob, Shahrin; Salam, Z.; Azli, N. A. (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper presents an analysis of double loop Pi-Fuzzy controller for a single phase inverter. The scheme comprises two feedback control loops arranged in a cascaded manner. The current in the filter inductor and voltage across the filter capacitor are sensed and fed back to the system to form the inner loop and the outer loop, respectively. Both loops are controlled by a discrete single input Pi-Fuzzy controller. It is derived using the "sign- distance" method, which simplifies fuzzy set into a single input single output system. The work analyses the effect of fuzzy control surface for both loops in improving large- signal performance of the controller. Based on the analysis, the replacement of single input PI Fuzzy for voltage loop with a simple discrete linear PI controller will be justified.